A cross-sectional study on the determinants of parents' giving vitamin C to their children engaged in sportive activities - Yücel, Ali Serdar; Korkmaz, Murat; Özpınar, Saliha; Öztaş, Dilek; Düz, Serkan; Cihaner, Perihan; Kuyucu, Mihalis (Michael) (Campus Educa Sportis S.l., 2026)
The primary objective of this study is to examine the sociodemographic determinants influencing parents' administration of vitamin C to children participating in sports activities. The research was conducted with the participation of 697 parents residing in various districts of Istanbul and having children aged 9–18 years. Data were collected using a questionnaire and analysed using logistic regression, chi-square test, t-test, and multiple regression analyses in the SPSS 25 programme. The child's regular vitamin C use was considered the dependent variable. The parents' educational level, income level, occupational status, and family structure were evaluated as independent variables. When evaluating the findings, we observed that as the level of education increased, parental awareness became more pronounced. In particular, we found that the rate of regular vitamin C use was significantly higher among children of parents with high income levels, university degrees, and office jobs (p<0.05). Another finding was that individuals who exercised regularly were more aware. It was also determined that vitamin C use is more prevalent among children who engage in significantly more weekly exercise and are younger in age (p<0.001). In conclusion, parents' socioeconomic and educational levels play a decisive role in children's immune support behaviours. These findings have the potential to contribute to the development of parent-focused educational programmes and health policies aimed at supporting children's health.

El objetivo principal de este estudio es examinar los determinantes sociodemográficos que influyen en la administración de vitamina C por parte de los padres a los niños que participan en actividades deportivas. La investigación se llevó a cabo con la participación de 697 padres residentes en diversos distritos de Estambul y con hijos de entre 9 y 18 años. Los datos se recopilaron mediante un cuestionario y se analizaron utilizando regresión logística, prueba de chi-cuadrado, prueba t y análisis de regresión múltiple en el programa SPSS 25. El consumo regular de vitamina C por parte del niño se consideró la variable dependiente. El nivel educativo de los padres, el nivel de ingresos, la situación laboral y la estructura familiar se evaluaron como variables independientes. Al evaluar los resultados, observamos que, a medida que aumentaba el nivel de educación, la conciencia de los padres se hacía más pronunciada. En particular, encontramos que la tasa de consumo regular de vitamina C era significativamente mayor entre los hijos de padres con altos niveles de ingresos, títulos universitarios y trabajos de oficina (p < 0,05). Otro hallazgo fue que las personas que hacían ejercicio regularmente eran más conscientes. También se determinó que el consumo de vitamina C es más frecuente entre los niños que realizan una cantidad significativamente mayor de ejercicio semanal y son más jóvenes (p<0,001). En conclusión, los niveles socioeconómicos y educativos de los padres desempeñan un papel decisivo en los comportamientos de apoyo inmunológico de los niños. Estos hallazgos pueden contribuir al desarrollo de programas educativos centrados en los padres y políticas sanitarias destinadas a apoyar la salud de los niños.
Estudio transversal sobre los factores determinantes de la administración de vitamina C por parte de los padres a sus hijos que realizan actividades deportivas
Keywords: vitamin c use; parental attitudes; sportive children; supplementary foods; consumo de vitamina c; actitudes de los padres; niños deportistas; alimentos complementarios